HUBUNGAN KEPERCAYAAN DAN PELAYANAN DENGAN KEPUTUSAN MENGGUNAKAN JASA CV. RAFELINDOTOUR AND TRAVEL BENGKULU - Tito Irwanto; Karona Cahya Susena; Putri Ramaddan (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2019)
The purpose of this study was to determine the relationship of trust and service with the decision to use the services of CV. Rafelindo tour and travel Bengkulu. Methods of data collection using questionnaires and analytical methods using Spearman rank correlation and hypothesis testing. The sample from this study was 100 consumers who bought tickets that were addressed at Jl. Cempaka No.007 RT / TW 007/003 Kel. KebunBelerKec.The Great Queen. Based on the results of the research the Spearman rank correlation of trustees has a correlation of 0.467 with the criteria of moderate assessment and service having a correlation of 0.602 with strong assessment criteria. This shows that the service is very much related to purchasing decisions, which means that the services that CV. Rafelindo tour and travel Bengkulu is getting higher, the decision to use services on CV. Rafelindo tour and travel Bengkulu. Hypothesis test results are known that tcount is greater than RHOl (0.467> 0.364 & 0.602> 0.478). Thus Ho1 & Ho2 are rejected and H1a1 & Ha2 are accepted. This means that trust and service have a significant relationship with the decision to use services on the CV. Rafelindo tour and travel Bengkulu.